WHY DO FEWER WOMEN THAN MEN APPLY FOR GRANTS AFTER THEIR PHDS?. Issue 3 (26th February 2018) - Goldstein, Lynne; Mills, Barbara J.; Herr, Sarah; Burkholder, Jo Ellen; Aiello, Leslie; Thornton, Christopher
Abstract : In spring 2013, the Society for American Archaeology created the Task Force on Gender Disparities in Archaeological Grant Submissions because of an apparent disparity in the rates of senior (post-PhD) proposal submissions by men and women to archaeology programs at the National Science Foundation (NSF) and the Wenner-Gren Foundation for Anthropological Research. Although NSF success rates for men and women between 2009 and 2013 were roughly equal, the number of senior women archaeology submissions was half that of men. Given the documented increase in the proportion of women in academic archaeology, this representation of women seemed low. Moreover, submissions for NSF doctoral dissertation improvement grants were evenly divided between men and women. Statistics for Wenner-Gren noted the same general disparity in archaeology. This study examines and integrates a variety of data sources, including interviews with post-PhD women, to determine whether or not there is a problem in research grant submissions. Although the results indicate that there is a problem, it is multifaceted. Women are not well represented at research-intensive universities, and some women instead practice what we term "scaffolding" to integrate smaller pots of money to accomplish their research. Recommendations are provided for female applicants, academic departments, the Society for American Archaeology, and granting agencies. Abstract : En la primavera de 2013 la Society for American Archaeology (SAA) creó el Equipo Especial de Disparidades de Género en las Presentaciones de Becas Arqueológicas debido a la aparente disparidad entre hombres y mujeres en las tasas de presentaciones de propuestas de alto nivel (posdoctorado) a programas de arqueología en la National Science Foundation (NSF) y la Wenner-Gren Foundation for Anthropological Research. Aunque las tasas de éxito de la NSF para hombres y mujeres de 2009 a 2013 fueron aproximadamente iguales, la cantidad de presentaciones de alto nivel sometidas por mujeres fue la mitad que por hombres. Dado el aumento documentado en la proporción de mujeres en la arqueología académica, esta representación de mujeres parecía baja. Además, las presentaciones para las becas de mejora de disertaciones doctorales de la NSF se dividieron equitativamente entre hombres y mujeres. Las estadísticas de la Wenner-Gren notaron la misma disparidad general en arqueología. Este estudio examina e integra una variedad de fuentes de datos, incluyendo entrevistas con mujeres de nivel posdoctoral, para determinar si hay un problema en las presentaciones para becas de investigación. Aunque los resultados indican la existencia de un problema, este es polifacético. Las mujeres no están bien representadas en las universidades de investigación intensiva, y algunas mujeres practican lo que llamamos "andamiaje", integrando pequeñas sumas de dinero para llevar a cabo su investigación. Se ofrecen recomendaciones para candidatas, departamentos académicos, la SAA y agencias otorgantes.